A Systematic Literature Review Analysis of the Culture of Politeness Among Junior High School Teenagers in the Digital Technology Era - Nordianus Wilfridus Bere Taek; Nurhatatti Fuad; Mohammad Sofwan Effendi; Syafaat Ariful Huda (FKIP - Universitas Riau, 2026)
This study analyzes how the culture of politeness among junior high school students is influenced in the digital technology era and identifies impactful educational strategies for developing adaptive ethical norms. The research employs a Systematic Literature Review (SLR) using the PRISMA approach, examining publications from 2020 to 2025 obtained through Publish or Perish from Scopus and Google Scholar databases. The literature selection process included identification, screening, eligibility, and in-depth analysis, resulting in 89 relevant articles. The findings indicate that students’ politeness culture extends beyond traditional norms, reflecting a dynamic process involving digital ethical literacy, parental and school supervision, social media influence, and technology integration in character development. Effective digital educational strategies show a significant correlation with increased politeness by shaping positive perceptions, strengthening normative credibility, and fostering respectful social relationships among adolescents, families, and school communities. These findings imply that nurturing politeness should be integrated into character management and digital communication education, providing guidance for policymakers and educators in strengthening ethical norms and students’ character in the digital era.